PENGGUNAAN KAYU JABON (Anthochepalus chinensis Lamk) DAN BALANGERAN (Shorea balangeran Korth) UNTUK KEBUTUHAN MASYARAKAT DAN INDUSTRI (Balangeran and Jabon Timber for Public and Industrial Purposes) - Effendi Arsad (Kementerian Perindustrian, 2016)
Jabon is a fast-growing perennials. The wood has smoother texture than Balangeran, cylinder and straight, yellowish - white color and non fibrous, and easy to peel. Jabon wood can be used as raw materials for: plywood industry, furniture, pulp, children toys, crates, sole, matches and non-construction building materials. Balangeran wood can be utilised for plywood industry, furniture and building materials, bridge, keel, railway sleeper and power pole. The heartwood is red-brown and dark brown colored, the sapwood is yellowish white color or pink, straight fibers, the texture is coarse and even, with glassy surface and contains resin, straight trunk. Jabon and balangeran wood can be developed for commercial wood substitution.Keywords : jabon, balangeran, timber, publics, industry